KAJIAN LUAS KAWASAN HUTAN SESUAI SK 2357/MENHUT-II/2004 DENGAN RENCANA TATA RUANG WILAYAH PROVINSI TAHUN 2010-2030. (Studi Kasus Di Balai Pemantapan Kawasan Hutan Wilayah XIII Pangkalpinang) - Wilya, Wirahadi; AT, Mulyadi; Lidiawati, Ina (Universitas Nusa Bangsa, 2014)
The purpose of this study is to compare the extent of forest area by map designation of forest areas SK.357 / Menhut-II / 2004 with Proposed map RTRWP years 2010-2030 as well as the intentions and objectives of the Local Government proposing changes to the designation and functions of forest areas. This study was conducted in Bangka Belitung Province from July 2015 through August 2015. The research method using the map data are from BPKH XIII Lists Pinang Forest Service Bangka Belitung Province and using purposive method to determine the intent and purpose of making provincial spatial plan The activities undertaken in this study include: interviews, as well as data processing and data analysis. Data collected in the form of primary data (vector data) and secondary data (general conditions of the location and study legislation on forestry and spatial). The technique of collecting primary data through interviews with respondents (staff BPKH and the Forest Service Bangka Belitung Province) while secondary data is done through the study of literature. Based on the research results, the calculation of the percentage of forest area with SK.357 / Menhut-II / 2004 in the amount of 40.54% and forests 39.35% RTRWP proposal. A reduction in forest area of 1.19%. Although the forest area was reduced, but it does not violate the laws - laws which mandate a minimum area to be preserved as a forest area is 30% of the land area. Counties that experienced the greatest changes that Belitung district while the districts with the fewest changes are Bangka Barat district.